Stability Test and Antioxidant Test of Peel-off Gel Mask of Butterfly Pea Flower Extract (Clitoria ternatea L.) Against Physical Characteristics - Setiyaningsih, Wahyu; Sudarsono, Agustina Putri Pitarisa; Istianingrum, Elisa (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
The telang flower plant (Clitoria ternatea L.), especially its flowers, contains high antioxidants. This antioxidant activity can inhibit free radicals and can function as anti-aging. Antioxidants are one of the components in cosmetics that are needed to be anti-radical. Therefore, researchers want to know the correct formulation for butterfly pea flower extract (Clitoria ternatea L.) as an antioxidant in peel-off gel mask preparations with varying concentrations of Polyvinyl Alcohol (PVA) and Hydroxypropyl Methylcellulose (HPMC). The research method used is an experimental method. This research includes extracting butterfly pea flowers using the maceration method with 70% ethanol. The manufacturing method is developed using hot aqua PVA and HPMC which is formulated into a Peel-Off gel mask. The peel-off gel mask preparations that have been made are tested for quality control which includes organoleptic test, homogeneity test, pH test, viscosity test, spreadability test, stickiness test, dry time test, and preference test. Peel-off masks with a variety of PVA and HPMC bases affect the viscosity, spreadability, adhesion and dry time test of peel-off gel mask preparations with ethanol extract of butterfly pea flowers.